Pengaruh Kepuasan Kerja, Resiliensi, Work Engagement Terhadap Komitmen Afektif Pekerja Milenial - Muchtadin (Haka Vyza Media, 2023)
The millennial generation is less attached to work and tends to want to leave work. This research aims to determine the effect of job satisfaction, resilience, work experience on affective commitment. Research was conducted on 100 millennial workers in Indonesia. Sampling was carried out using convenience sampling. The data analysis method was carried out using PLS SEM. Data collection was carried out via Google form via various social media. The research results show that job satisfaction, resilience, and work engagement each have a positive effect on the affective commitment of millennial workers. Future research could also be limited to worker status and organization type. This research contributes to increasing affective commitment through factors such as job satisfaction, resilience and work engagement among millennial workers in Indonesia.